Bibliometric analysis of social media persuasiveness and influence: a comprehensive review from 2010 to 2023 - Arfan Rehman Sherief; Arun Kumar Tarofder; Aidarus Mohamed Ibrahim; Raja Irfan Sabir; Muhammad Ahmad; Asad Ur Rahman (Cogent Business & Management)
As part of this bibliometric analysis, the literature on social media persuasiveness and influence is examined between 2010 and 2023. This study explores academic output, influential publications, authors, institutions, and countries in this field by utilising bibliometric analyses, performance analyses, and thematic clustering. 195 documents are retrieved from SCOPUS and are analysed using VOSviewer for thematic clustering and performance analysis. According to the findings, 2022 was the most productive year for social media impact and persuasiveness publications. It was reported that the School of Management of the University of Science and Technology of China, the Management School at Anhui University, and the Department of Finance and Decision Sciences at Hong Kong Baptist University received a total of 376 citations. The most cited article was ‘Examining the Influence of Online Reviews on Consumers’ Decision-making: A Heuristic-Systematic Model’’, which received 376 citations among the top five journals. This study provides valuable insights for researchers, practitioners, and policymakers interested in leveraging social media’s persuasive capabilities. It does so by identifying six distinct clusters within the literature.